Formation of scientific foundations for system monitoring under conditions of spatial and functional transformation of urbanized areas - KRYVDA, Kyrylo (Ways to Improve Construction Efficiency, 2025)
System monitoring of urbanized areas emerges as a fundamental component of managing contemporary cities, where spatial and functional processes evolve with unprecedented speed and complexity. Its essence lies in the creation of a unified information and analytical environment that integrates ecological, social, engineering, and managerial parameters of urban development. Monitoring ensures continuous feedback between environmental dynamics and managerial decisions, forming the basis for forecasting, adaptation, and the adjustment of spatial strategies. In the digital era, this function expands through the use of Geographic Information Systems (GIS), sensor networks, satellite observation technologies, artificial intelligence, and cloud platforms that enable the integration of multi-level data in real time. System monitoring of urban space takes on the features of an adaptive system capable of identifying trends, assessing relationships between spatial changes and socio-economic processes, and determining critical points of development. Its structure is based on the principles of systematization, continuity, scalability, integration, and flexibility. The core idea is that observation of the city should not be limited to recording its current state but should evolve into an intelligent mechanism for prediction and decision support. This approach transforms the role of monitoring – from a purely technical control tool into a strategic element of urban management. Within the framework of spatial and functional transformation, system monitoring serves as a mechanism for balancing development, resilience, and environmental comfort. Its implementation enables timely responses to change, assessment of resource efficiency, identification of potential risks, and optimization of the urban spatial structure. The modern city functions as a complex, multi-level system in which every decision affects the environment, infrastructure, and quality of life. In this context, system monitoring becomes not only a technological platform but also a scientific concept that combines analysis, forecasting, and management into a single model. Its mission is to ensure the sustainable, safe, and flexible development of urban areas, where data become a strategic resource for shaping the future.